Solution In Degenerate Ordinary Systems Of Differential Equations By The Differential Sweep Method (Global Scientific Review, 2023)
In this article, we consider a system of degenerate ordinary differential equations. A calculation method using simple factorization is proposed. The existence of a solution to the boundary value problem is proved, an algorithm for friction of the problem is constructed, and a uniform estimate for the solution is obtained using the maximum principle method.